Evidence for a mediator of RNA polymerase II transcriptional regulation conserved from yeast to man. - Boube, M.; Joulia, L.; Cribbs, D.L.; Bourbon, H.M. (Cell, 2002)
Mediator complexes (MED) link transcriptional regulators to RNA polymerase II. Here, we summarize the latest advances on the functional organization of yeast Mediator. We argue for the existence of a "universal" Mediator structurally conserved from yeast to man, based on an extensive analysis of sequence databases. Finally, we examine the implications of these observations for the physiological roles of metazoan MED subunits.